(untitled) (Ciudades, 2017)
Since the Vienna Memorandum, and after six years of expert meetings and debates, it is programmed that UNESCO’s General Conference adopts at its 36th session, in autumn 2011, a Recommendation which proposes a new approximation to urban historic ensembles conservation. The historic urban landscape means to adapt conservation of urban heritage according to the requirements of the sustainability, and advance towards an integrated consideration of different heritage kinds and its accounts. But at same time it generates serious problems of interpretation and application. The term “landscape” is in fashion, and it allows to embrace numerous aspects with one word; there are so many that the term becomes imprecise, difficult to apply, and easy to distort. On the other hand, historic urban landscape is proposed as an answer to ‘new’ problems of urban ensembles conservation; but in its proposal is lacking the critic reflection in regards to the social issue (how to revitalize, without gentrifying, the historic urban ensemble) that, established decades ago, is far from being solved.